DESIGN AND CONSTRUCTION OF COMMUNITY BASED FLOATING DOCK IN PARIT ISLAND, KARIMUN DISTRICT, RIAU ISLANDS, INDONESIA - Rildova Rildova; Eko Charnius Ilman; Hakam Hekmatyar Akhmad Barani; Rusdianto Efenddi; Endra Susila; Taufik Taufikurahman (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2024)
Many Indonesian islands lack essential inter-island crossing facilities, posing challenges for small island communities' livelihoods. This study addresses the need for accessible docking facilities in Parit Island, Riau Islands, using a community-based floating dock approach. It is chosen due to relatively high tides conditions onsite. The project began with site-specific metocean analysis and extensive stakeholder consultations, ensuring alignment with community aspirations. Eco-friendly materials like wooden frames and plastic drums were used for simplicity and sustainability in dock construction. Local artisans and laborers were engaged, promoting community involvement and economic empowerment. This paper delves into dock design, stability, piling systems, and accessibility. The completed community-based floating dock enhances local living standards and regional trade. It serves as a model for straightforward infrastructure development in island communities, emphasizing community engagement, environmental responsibility, and socioeconomic progress.